The effect of retained austenite stability on the formability of third generation advanced high strength steel - Yim Gihak; Shin Heegwon; Kim Hyejin; Jung Seungpill; Jeon Jinhwa; Lee Dongyul (MATEC Web of Conferences)
This study aims to evaluate the effect of retained austenite (RA) stability on the performance of third-generation advanced high-strength steel (AHSS). The analysis focuses on two quenching and partitioning (Q&P) steels with a minimum tensile strength designation above 1.0 GPa. Additionally, two conventional dual-phase (DP) steels with tensile strengths of 780 MPa and 1.0 GPa were included for comparison. The retained austenite stability of the Q&P steels was first assessed through tensile testing by observing changes in the retained austenite volume fraction. Subsequently, its impact on formability was investigated by comparing formability parameters, including instantaneous n-values, hole expansion ratio (HER), limit drawing ratio (LDR), bending angle, and forming limit curve (FLC). Furthermore, a hydrogen-induced cracking (HIC) test was conducted on drawn cups to explore the relationship between retained austenite stability and resistance to hydrogen embrittlement. The results demonstrate that the stability of retained austenite plays a significant role in determining the overall formability and performance of third generation AHSS.